PENGARUH PENGHARGAAN DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU - Kasmin, Kasmin (Idaarah: Jurnal Manajemen Pendidikan, 2019)
Abstract: This study aims to find out how the leadership and respect of principals at Aroeppala Makassar Elementary School, how the teacher's performance at Aroeppala Makassar Elementary School, and how much influence the principal's leadership and appreciation has on the performance of teachers at Aroeppala Makassar Elementary School. This research is a quantitative study with an ex post facto type of research. Data collection methods used were observation, interviews, and questionnaires. Based on the results of the study it can be concluded that the headmaster's award and leadership are in the high category based on a total score of 52-70 (high category), the performance of teachers at Makassar Aroeppala Elementary School is in the high category based on a total score of 52-70 (high category); and the principal's appreciation and leadership has a positive effect on the performance of teachers in Makassar's Aroeppala Elementary School with a contribution of 61%.